Measurement of instantaneous Achilles tendon moment arm and force during the stance phase of running - Krikelis, G.; Pain, M. T. G.; Furlong, L.-A. M. (Computer Methods in Biomechanics and Biomedical Engineering, 2021)
Accurate estimates of the Achilles tendon (AT) moment arm (ATMA) are necessary for investigating triceps surae muscle-tendon unit loading and function. There are limited reported values of ATMA during running. By combining ultrasound and motion capture, ATMA was estimated during the stance phase of running. Group mean ATMA was estimated at 49.2 ± 3.8 mm and 37.5 ± 5.3 mm, relative to the centre of rotation (malleoli markers midpoint) and the ankle finite helical axis respectively. Differences in the corresponding estimated AT forces reached up to 3100 N approximately. Such discrepancies can lead to misinterpretation of the whole muscle-tendon unit function.